A positive feedback loop between Wnt/β‐catenin signaling and hTERT regulates the cancer stem cell‐like traits in radioresistant nasopharyngeal carcinoma cells. Issue 11 (17th February 2020) - Chen, Kaihua; Chen, Li; Li, Ling; Qu, Song; Yu, Binbin; Sun, Yongchu; Wan, Fangzhu; Chen, Xishan; Liang, Renba; Zhu, Xiaodong
Abstract: Radioresistance may be induced by cancer stem cells (CSCs), while the biological traits of CSCs need to be retained by telomerase. The telomerase activity mainly depends on the transcriptional regulation of human telomerase reverse transcriptase (hTERT). Moreover, Wnt/β‐catenin signaling is also considered essential for maintaining the CSC phenotypes. In the previous study, we discovered that the radioresistant nasopharyngeal carcinoma cells CNE‐2R displayed CSC‐like traits, as well as high expression of hTERT and β‐catenin, but whether hTERT and β‐catenin were involved in regulating the CSC‐like traits and radiosensitivity of CNE‐2R cells remained unclear. In this study, our results suggested that hTERT could positively regulate the expression of CSC‐related proteins, as well as the cytoplasm‐ and nucleus‐β‐catenin, but it could not markedly regulate the expression of total β‐catenin in CNE‐2R cells. Meanwhile, Wnt/β‐catenin signaling had a positive regulatory effect on the expression of hTERT and CSC‐related proteins. Moreover, there was a β‐catenin/hTERT protein complex in CNE‐2R cells, indicating that β‐catenin could directly interact with hTERT protein. Our results also revealed that silencing hTERT or suppressing Wnt/β‐catenin signaling could attenuate telomerase activity and radioresistance of CNE‐2R cells; while suppressing Wnt/β‐catenin signaling, the telomerase activity and radioresistance could be reversed through overexpressing hTERT. Taken together, we have outlined a positive feedback loop between Wnt/β‐catenin signaling and hTERT in CNE‐2R cells, which can regulate the telomerase activity and CSC‐like traits, thus regulating the radiosensitivity. Therefore, blocking Wnt/β‐catenin signaling transduction and interfering with hTERT expression may be a promising approach for targeting radioresistant nasopharyngeal carcinoma cells with CSC‐like traits. Abstract : This paper has outlined a positive feedback loop between Wnt/β‐catenin signaling and human telomerase reverse transcriptase (hTERT) in radioresistant nasopharyngeal carcinoma cell line CNE‐2R, which can regulate the telomerase activity and cancer stem cell (CSC)‐like traits, thus regulating the radiosensitivity of CNE‐2R cells.